Harry Potter and the half-blood prince [compact disc, unabridged] - Rowling, J. K. (Rowling, J. K. Year ... at Hogwarts ;, 2005)
Harry Potter and the Half-Blood Prince takes up the story of Harry Potter's sixth year at Hogwarts School of Witchcraft and Wizardry at this point in the midst of the storm of this battle of good and evil.